Ideology of Rohis Activities and Its Implications on Student Learning Outcomes in Islamic Education at Public Senior High School 3 Kotamobagu - Amiruddin, Amiruddin; Bahansubu, Hardianto; Mania, Sitti; Rasyid, Akbar (Jurnal Ilmiah Iqra', 2024)
This article examines the Ideology of Rohis Activities and Its Implications on Students’ Learning Outcomes in Islamic Religious Education at SMA Negeri 3 Kotamobagu. The research questions are: 1) What is the concept of Islamic ideology in implementing Rohis religious activities at SMA Negeri 3 Kotamobagu? 2) How do Rohis religious activities affect students’ learning outcomes in Islamic Religious Education at SMA Negeri 3 Kotamobagu? Rohis activities are always carried out every Friday at 7:00 am, which consist of three programs: 1) Acceptance of Islamic Studies, 2) Recitation of Dzikir Rotibul Hadad and Asmaul Husna, and 3) Recitation of Quranic verses and Quranic reading improvement. This research uses a qualitative approach; data is collected through observation, interviews, and documentation. Data collection is used to obtain primary and secondary data, which are then analyzed using data reduction, data presentation, and conclusion drawing.The study results show that 1) The Rohis activities at SMA Negeri 3 Kotamobagu use a multiculturalism ideology. This result is strongly supported by primary and secondary data obtained by the author. The primary data consists of direct interviews, survey results, and multiculturalism questionnaires given to key informants such as Rohis supervisors, Islamic Religious Education teachers, his leaders, and students. 2) The implications of Rohis activities at SMA Negeri 3 Kotamobagu Positively impact students’ cognitive abilities and exam results in Islamic Religious Education at SMA Negeri 3 Kotamobagu. This result is also strongly supported by primary and secondary data. The primary data consists of direct interviews, survey results, and questionnaires given to respondents, including Rohis supervisors, Islamic Religious Education teachers, Rohis leaders, and students in grades X-XII